2016
DOI: 10.14348/molcells.2016.2286
|View full text |Cite
|
Sign up to set email alerts
|

Design of a RANK-Mimetic Peptide Inhibitor of Osteoclastogenesis with Enhanced RANKL-Binding Affinity

Jeonghwan Hur,
Ambarnil Ghosh,
Kabsun Kim
et al.

Abstract: The receptor activator of nuclear factor κB (RANK) and its ligand RANKL are key regulators of osteoclastogenesis and well-recognized targets in developing treatments for bone disorders associated with excessive bone resorption, such as osteoporosis. Our previous work on the structure of the RANK-RANKL complex revealed that Loop3 of RANK, specifically the non-canonical disulfide bond at the tip, performs a crucial role in specific recognition of RANKL. It also demonstrated that peptide mimics of Loop3 were capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Besides binding RANK, OPG is able to interact with TRAIL and induces apoptosis of tumor cells through the cell-surface receptors death receptor 4 (DR4) and DR5 in the TNFRSF family [9]. The binding mode to RANKL was determined from computational docking and molecular dynamics simulations [10,11]. OPG is expressed in vivo by ECs, VSMCs, and osteoblasts.…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…Besides binding RANK, OPG is able to interact with TRAIL and induces apoptosis of tumor cells through the cell-surface receptors death receptor 4 (DR4) and DR5 in the TNFRSF family [9]. The binding mode to RANKL was determined from computational docking and molecular dynamics simulations [10,11]. OPG is expressed in vivo by ECs, VSMCs, and osteoblasts.…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…For these reasons, the use of small molecules which are able to target remodeling pathways has been advocated [ 12 ]. To this end, peptides such as the gap-junction protein (connexin 43) mimetic (GAP27) [ 13 ], the RANK-mimetic peptide [ 14 ], the OPG-mimetic peptides [ 15 ], the TNF-[alpha] and the RANKL antagonist peptide [ 16 ], and a TNF receptor loop peptide mimic [ 17 ] have been identified as able to reduce bone resorption and/or promote bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Hur et al recently reported the synthesis of a peptide inhibitor with enhanced RANKL affinity for osteoclastogenesis. In their work, they present experimental data along with a computational molecular dynamic and a docking study.…”
Section: Introductionmentioning
confidence: 99%